Scandinavian Countries. - Conley; Ondrick; Wray (Fort Leavenworth, KS : US Army Command and General Staff College, 1946)
Seeks to determine the capabilities and limitations of the Scandinavian Countries in world affair in general, and in relation to the foreign relations of the United States in particular.